(untitled) (Revista Médica de Trujillo, 2026)
Objective: The objective was to deepen the understanding of the morphology of the grooves present on the proximal surfaces of the roots of permanent anterior teeth, both maxillary and mandibular, and to evaluate the relationship between their presence or absence and periodontal attachment loss. Materials and methods: Proximal root grooves were analyzed in 150 extracted maxillary and mandibular anterior teeth. To assess periodontal attachment loss, root surfaces were stained with 0.1% toluidine blue. In addition, the relationship between the presence or absence of grooves and the degree of periodontal attachment loss was examined. Results: The prevalence of proximal root grooves was 86.67%. In maxillary teeth, the prevalence was 43.42%, while in mandibular teeth it reached 56.67%. Surfaces with grooves were found to have greater attachment loss compared to those without grooves. Conclusion: Proximal root grooves are identified as a relevant local etiological factor in periodontal attachment loss, highlighting the need to consider them in the diagnosis, prognosis, and planning of periodontal treatment.